2021
DOI: 10.7554/elife.62161
|View full text |Cite
|
Sign up to set email alerts
|

Human ORC/MCM density is low in active genes and correlates with replication time but does not delimit initiation zones

Abstract: Eukaryotic DNA replication initiates during S phase from origins that have been licensed in the preceding G1 phase. Here, we compare ChIP-seq profiles of the licensing factors Orc2, Orc3, Mcm3, and Mcm7 with gene expression, replication timing and fork directionality profiles obtained by RNA-seq, Repli-seq and OK-seq. ORC and MCM are significantly and homogeneously depleted from transcribed genes, enriched at gene promoters, and more abundant in early- than in late-replicating domains. Surprisingly, after cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 108 publications
(173 reference statements)
6
45
0
Order By: Relevance
“…It was also recently revealed that ORC density is correlated with replication timing. ORC was observed to preferentially bind to early-replicating chromatin regions and transcription start sites of actively transcribed genes [ 99 ]. Furthermore, the proteins DONSON and FANCM are associated with euchromatin replicated early in the S-phase and heterochromatin replicated in the late S-phase, respectively [ 100 ].…”
Section: Other Sources Of Replication Stress During Replication and Their Potential Relation-ship With Replication Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also recently revealed that ORC density is correlated with replication timing. ORC was observed to preferentially bind to early-replicating chromatin regions and transcription start sites of actively transcribed genes [ 99 ]. Furthermore, the proteins DONSON and FANCM are associated with euchromatin replicated early in the S-phase and heterochromatin replicated in the late S-phase, respectively [ 100 ].…”
Section: Other Sources Of Replication Stress During Replication and Their Potential Relation-ship With Replication Timingmentioning
confidence: 99%
“…Similar works need to extend these studies to mammalian cells. Nonetheless, a recent genome-wide analysis of the ORC/MCM distribution performed in human cells has weakened the role of ORC and MCM proteins in the regulation of the RT program [ 99 ]. It would thus be informative to observe the RT profiles of human cells with mutations/deregulation in/of ORC and MCM genes to directly assess their roles in the RT program, especially since ORC and MCM mutations have been observed in human diseases including cancers (reviewed in [ 139 , 140 ]).…”
Section: Causes Of Replication Timing Changes In Cancersmentioning
confidence: 99%
“…As a result, heterochromatin loading lags behind euchromatin in early G1, but differential acceleration allows heterochromatin to “catch up” with euchromatin by the end of G1. Other studies of MCM binding sites in mammalian cells also report similar overall loading in both transcriptionally active and repressed genomic loci which generally correlate with euchromatin and heterochromatin respectively 18, 60 .…”
Section: Discussionmentioning
confidence: 53%
“…In many species, replication timing in S phase shows a general (though not exclusive) pattern of early euchromatin replication and late heterochromatin replication 71, 72 . Differences in the density of G1 MCM loading at different individual loci have been implicated in these S phase replication timing differences; more ORC or MCM loading in G1 correlates with early firing origins 17, 60, 73 . Early firing in S and early G1 origin licensing may both be consequences of general DNA accessibility in euchromatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation